2012 Olympic performance assessment - a European perspective - Dick, F. (New Studies in Athletics, 2012)
Planning based on effective debriefing and the practical lessons learned from experiences is the key to sustainable success in any endeavour. As the pinnacle of the competitive challenge for any athlete, the Olympic Games are both an end in themselves and the focus of planning for delivering performance and results objectives. Debriefing after the Games or other major championships and then planning for the next edition are a primary responsibility of national athletics federations and their personnel, particularly the Chief Coach or Performance Director. This article, adapted from a report prepared for European Athletics, provides a documented context for debriefing after the 2012 Olympic Games by bringing together technical and statistical analyses of the athletics events that took place in London. Written by an experienced former head coach, it includes a unique analysis of performance delivery "on the day" that can be used as an indicator of the effectiveness of high-performance policies, coaching and support at the national level. A key finding is that European teams generally did not deliver as effectively as the teams from the USA and Jamaica. The report concludes with ten initial recommendations for federation policy makers, performance directors and elite coaches to consider